MBCL-18. CHEK2 MUTATION IN HIGH-RISK MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Shah, Nidhi; Walter, Andrew
Abstract: Childhood cancer remains the leading cause of non-accidental death in children, with brain and central nervous system malignancies comprising about 18% of new diagnoses each year. Combination therapy, including surgery, chemotherapy and radiation therapy in standard-risk medulloblastoma has led to cure rates of 80% or better. The 20% of tumors that do not respond to traditional therapies, or relapse early, could be due to activation of tumor predisposition genes. CHEK2 is cell cycle checkpoint kinase 2, a tumor suppressor gene associated with increased risk of malignancies, most commonly breast and prostate cancer. Here we discuss a case of medulloblastoma, with evidence of germline and tumor CHEK2 mutation. This 4 year-old child was initially treated with surgery, achieving gross total resection, chemotherapy, tandem stem cell rescue, as well as local radiation therapy to posterior fossa. One year after completion of therapy, she relapsed with disease outside of the radiation field. Next generation sequencing of the whole genome performed on tumor tissue resulted in CHEK2 T367 mutation in the absence of TP53 mutation, or other mutations of known tumor suppressor genes. TP53 mutation is a cancer predisposition syndrome, associated with Li Fraumeni syndrome. CHEK2 mutation has been associated with worse progression-free survival in cases of non-Hodgkin's lymphoma. Thus far, there have been no reported primary brain and central nervous system malignancies associated with CHEK2 mutation. This finding of CHEK2 mutation in medulloblastoma further supports the need for next generation sequencing on high-risk tumor types to predict response to therapy and overall prognosis.